2001
DOI: 10.1046/j.1365-2141.2001.02524.x
|View full text |Cite
|
Sign up to set email alerts
|

High levels of reticulated platelets and thrombopoietin characterize fetal thrombopoiesis

Abstract: Summary. To characterize fetal thrombopoiesis, we determined plasma thrombopoietin (TPO) and glycocalicin levels, platelet counts and reticulated platelets (RP) of fetuses and compared them with the respective values of their mothers. Percutaneous umbilical vein sampling in abnormal pregnancies revealed twofold higher thrombopoietin levels and 20-fold higher reticulated platelet counts, but lower levels of glycocalicin in fetuses compared with their mothers (P , 0´05). Neither the expression of platelet glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
3
15
0
3
Order By: Relevance
“…Our studies showed no change in derived platelet half-life after megakaryocytes were grown in the presence of two inhibitors of ADAM17, GM6001 and TAP-1 (Supplemental Figure 2, A and B). An alternative explanation for the shortened half-life is that most of our studies were performed with FL megakaryocytes, and fetal platelets have a shorter half-life compared with adult platelets (18). However, cultured infused adult BM megakaryocytes produced a similar delay in appearance and short half-life ( Figure 1F).…”
Section: Resultsmentioning
confidence: 83%
“…Our studies showed no change in derived platelet half-life after megakaryocytes were grown in the presence of two inhibitors of ADAM17, GM6001 and TAP-1 (Supplemental Figure 2, A and B). An alternative explanation for the shortened half-life is that most of our studies were performed with FL megakaryocytes, and fetal platelets have a shorter half-life compared with adult platelets (18). However, cultured infused adult BM megakaryocytes produced a similar delay in appearance and short half-life ( Figure 1F).…”
Section: Resultsmentioning
confidence: 83%
“…von Willebrand factor antigen level (VWF‐Ag) was measured with a fully automated simultaneous thermal analyser (STA) using the VWF‐Liatest (Diagnostica Stago, Paris, France), because VWF‐Ag levels influence CEPI‐CT values. Surface expression of GpIb (CD42b) was measured by flow cytometry from whole citrated blood as described previously (Jilma‐Stohlawetz et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The reduced quantity and/ or longevity of platelets generated in vitro from ES (or G1ME2) cell-and FL-derived megakaryocytes could be due to suboptimal culture conditions that fail to support full maturation. Alternatively, megakaryocytes from ES cells and fetal tissues are biologically distinct from adult megakaryocytes and their platelet progeny may have inherently reduced life spans (28)(29)(30). Human ES cell-derived megakaryocytes are believed to approximate those derived from early embryonic yolk sacs (31).…”
Section: Methodsmentioning
confidence: 99%